Collaboration in the Mexican Pharmaceutical Industry: An Analysis within the Institutional Framework - José G. Vargas Hernández; Alma Isela Rodríguez Hernández (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2017)
The objective of this study is to analyze the collaboration networks of the Mexican pharmaceutical industry from an institutional approach. The pharmaceutical sector at a global level is characterized by a high dynamism in innovation and collaboration. One could say that the high value recorded by the industry is due to this. However, in Mexico the lack of efficient institutions that ensure the appropriation of profits for investment in research within the industry are not perceived, this situation leads us to the next question, What is the dynamics of collaboration between pharmaceutical companies in Mexico? To answer this question, a database was created which identifies the alliances of the companies belonging to the Canifarma. Finally, a comparison of the number of registrations and patent applications between eight of these companies is made to measure the results of this situation.